(untitled) (Quinto Sol, 2020)
Pluralitas non est ponenda sine necessitate -“plurality should not be posed without necessity”- states the famous dictum. In a curious case of metabasis, it seems to apply nowhere best than in contemporary health care: the approach that unfolded as an offshoot of modern science in the West became so pervasive that is now globally known as ‘conventional’ medicine. This seems to be also the perception of scholars -historians, social medicine experts, among many others- who have stressed the global spread of Western medicine, while allowing for some footnotes on the ‘arrival’ of other approaches, which nonetheless remain ‘alternative’ or, in the best of cases, ‘complementary’ to mainstream health care. Integration of cultural traditions, however, is increasingly gaining territory and visibility. One striking example is provided by endeavors to make the various health care traditions communicate, no longer within a relationship of subordination, but as equally contributing to the general goals of promoting, maintaining and helping recover physical, mental and social health. In this paper I address the effort to create a common conceptual and methodological frame within the World Health Organization (WHO) initiative to develop a classification to enable the involved actors understand global and local trends. My particular focus is on the recent (May 2019) inclusion of Traditional Medicine conditions in the International Statistical Classification of Diseases and Related Health Problems, 11th revision–ICD-11, effective starting 1 January 2022.